DIFFERENT PROTEIN LEVELS ON EGG PRODUCTION AND HATCHABILITY IN BRONZ TURKEYS - Erisir, Z.; Gurdogan, F.; Yildiz, N. (Indian Veterinary Journal, 2008)
Turkeys fed diets containing 14-17% crude protein had higher performance and egg production when compared to turkeys fed diets containing 10-12% crude protein, (Meyer 1980). Hence, study was undertaken on the effects of different levels of protein on egg production and hatachability in Bronze Turkeys.